The Empowering Effect of Digital Transformation on Corporate ESG Performance: A Case Study of the New Energy Industry - Sun, Wenyi (Asia Pacific Economic and Management Review, 2025)
In the context of the global pursuit of sustainable development, the New Energy industry stands at the forefront of the green transition. Simultaneously, digital transformation (DT) has become a pivotal force reshaping corporate operations. This study investigates the synergistic interplay between these two megatrends, specifically exploring the empowering effect of corporate digital transformation on Environmental, Social, and Governance (ESG) performance within the new energy sector. Grounded in dynamic capability theory and stakeholder theory, this paper constructs a conceptual framework analyzing how DT acts as a technological enabler across the E, S, and G dimensions. Through a qualitative analysis of leading global new energy companies, including contemporary giants, the research identifies three primary pathways of empowerment: 1) Environmental Enhancement through smart energy management, predictive maintenance, and circular economy optimization; 2) Social Empowerment via bolstered occupational health and safety, supply chain transparency, and community engagement; and 3) Governance Improvement by enabling data-driven decision-making, enhancing risk management, and boosting information transparency. The findings reveal that DT is not merely a supportive tool but a transformative force that amplifies the intrinsic sustainability potential of new energy firms. However, the implementation is fraught with challenges, including high upfront costs, data security risks, and the digital skills gap. This paper concludes that a strategic, integrated approach to DT is crucial for new energy companies to fully unlock their ESG potential, thereby securing long-term competitiveness and investor confidence in an increasingly sustainability-oriented market.